Effect of colostrum given within the 12 hours after birth on feeding outcome, morbidity and mortality in very low birth weight infants: a prospective cohort study - Bashir, Tanveer (Sudan J Paediatr, 2019)
The current study aims to compare the feeding outcome, morbidity and mortality in very low birth weight (VLBW) infants who received early colostrum (<12 hours of life) and those who did not. All VLBW infants admitted to neonatal intensive care unit (NICU) were eligible for the study. Eligible infants were enrolled after obtaining written informed consent from either of the parents. Newborns who received colostrum within the first 12 hours after birth formed the study cohort and all others the control cohort. Both cohorts were followed till discharge from NICU. During the study period, 205 VLBW infants were admitted in NICU of whom 171 (83%) infants were enrolled in the study. Both study groups were comparable for mean birth weight, mean gestation and male sex. The proportion of infants with abnormal Doppler was significantly higher in the control group. All outcomes were adjusted for antenatal Doppler abnormalities. The primary outcome of time to reach full feeds in the study population was 6.90 ± 4.4 days as compared to 9.80 ± 4.86 days in the control group with a significant weighted mean difference of −2.4 (−0.8 to −3.9) days. Duration of total parenteral nutrition (TPN) days and mortality were all lower in the study cohort. Risk of sepsis and necrotising enterocolitis was similar in the both groups. Enteral colostrum within first 12 hours of birth in VLBW infants reduces the time to reach full feeds, TPN days and mortality.